SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMILIHAN METODE KONTRASEPSI PADA PASANGAN USIA SUBUR DENGAN ALGORITMA K-NEAREST NEIGHBOUR (KKN) - Christian Gratia Nugroho, Didik Nugroho, Sri Hariyati Fitriasih (Jurnal Ilmiah SINUS, 2015)
The research report titled "Decision Support System For Contraceptive Method Selection On Fertile Age Couple With AlgoritmaK- Nearest Neighbor (KNN). The method of collecting the data in this report is derived from data sources UCI Machine Learning Repository, and then perform system analysis is to perform modeling, perform inputs to the criteria established by providing specific score with scale figures. The next step is the calculation using k-Nearest Neighbour algorithm that provides results in the form of recommendations contraceptive methods to couples of reproductive age that will be used as consideration for the selection of contraceptive methods. Results of this research is a website interface, and both functional testing system and testing the validity of the system. The result of functional testing system, applications can run smoothly according to the procedures and the results of testing the validity of the data system KNN performed with 105 training data and testing the data 20, which was tested by the search formula SPK performance values obtained accuracy of 95% with no change in the data record training. Possible accuracy is increased when the amount of training data is increased to more. Keywords: C4.5 algorithm, Decision Supporting System, Reproductions Age, Contraceptive.